DAGING HALAL DAN THOYYIB - Muhammad Askari Zakariah (Jurnal Syariah Hukum Islam, 2018)
The objective of this study was determined to halal and good (thoyyib) in food and feed. Halal on plate and halal on production is one of term were used on this research. The term halal on plater is view from substrate, then halal on production is view from process include a slaughtering process until marketing. Critical control point for decided a meat halal is nine (9) point from handle a cattle until labeling. Some causes in area outer Kolaka Regency was showed that The marketer mixed or added a non halal meat to halal (meat) product.